Lawyers of the right professionalizing the conservative coalition - Southworth, Ann. (Chicago, Ill. : University of Chicago Press, 2008)
A multifacted portrait of the lawyers who serve the diverse constituancies of the conservative movement, 'Lawyers of the Right' explains what unites and divides lawyers for the three major groups - social conservatives, libertarians and business advocates - that have coalesced behind the Republican party.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cause lawyers -- United States; Lawyers -- United States -- Political activity; Conservatism -- United States; Law; United States of America, USA; Politics & government; Conservatism & right-of-centre democratic ideologies; Law & society, sociology of law; Legal profession: general